2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944254
|View full text |Cite
|
Sign up to set email alerts
|

Towards a multimodal bioelectrical framework for the online mental workload evaluation

Abstract: In this study, a framework able to classify online different levels of mental workload induced during a simulated flight by using the combination of the Electroencephalogram (EEG) and the Heart Rate (HR) biosignals has been proposed. Ten healthy subjects were involved in the experimental protocol, performing the NASA - Multi Attribute Task Battery (MATB) over three different difficulty levels in order to simulate three classic showcases in a flight scene (cruise flight phase, flight level maintaining, and emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Similar research has been conducted in other fields, such as HCI, driving, and flight control. The performance trends of individual sensors in this study were aligned with the findings from other areas, such as driving [87,88], flight control [90], first-person shooting simulation [95], and so on. When setting up the workload prediction algorithm, the specific domain information was not used explicitly in training, therefore, this approach may be generalizable to other domains.…”
Section: Model Generalizationssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar research has been conducted in other fields, such as HCI, driving, and flight control. The performance trends of individual sensors in this study were aligned with the findings from other areas, such as driving [87,88], flight control [90], first-person shooting simulation [95], and so on. When setting up the workload prediction algorithm, the specific domain information was not used explicitly in training, therefore, this approach may be generalizable to other domains.…”
Section: Model Generalizationssupporting
confidence: 77%
“…This suggests that EEG is the most predictive modality for characterizing workload levels. Other studies in domains outside of RAS [55,[87][88][89][90] also concluded that EEG was the salient modality for workload characterization. In RAS, EEG may be especially reliable due to the design of the dVSS.…”
Section: Fusionmentioning
confidence: 94%
“…More recently, Shou et al (2012) found that “the frontal theta EEG activity was a sensitive and reliable metric to assess workload […] during an ATC task at the resolution of minute (s).” The same findings have been highlighted by Borghini et al (2013) involving pilots in flight simulation tasks. In other recent studies involving ATCOs (Aricò et al, 2013, 2014, 2015b,c; Borghini et al, 2014; Di Flumeri et al, 2015; Toppi et al, 2016), it was demonstrated how it was possible to compute an EEG-based Workload Index able to significantly discriminate the workload demands of the ATM task, and to monitor them continuously by using frontal-parietal brain features. Other studies about the mental workload estimation by using neurophysiological indexes, have been proposed also in other operational contexts (Car drivers - Kohlmorgen et al, 2007; Borghini et al, 2012a; military domain - Dorneich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Between the two, the EEG is usually preferred for the workload assessment for its high temporal resolution. Moreover, it has been proved that EEG features provide higher accuracy respect to ECG and GSR ones [18], [19].…”
Section: Workload Measurementsmentioning
confidence: 99%